Advancing One Health through veterinary education: a mixed methods needs assessment for implementing a WOAH-harmonized national veterinary medicine curriculum in Ethiopia - Bessler, Andrea L.; Hoet, Armando E.; Nigatu, Shimelis; Swisher, Samantha; Fentie, Tsegaw; Admassu, Bemrew; Molla, Adugna; Brown, Manon; Berrian, Amanda M. (Frontiers in Veterinary Science, 2024)
International organizations now actively promote and implement One Health collaborative approaches to prevent, detect, and control diseases in humans and animals, recognizing the critical importance of the veterinary and agricultural sectors. Moreover, Veterinary Services are chronically under-resourced, especially in low-and middle-income countries. Given the importance of National Veterinary Services to food security, nutrition, poverty alleviation, and global health security, strengthening veterinary capacity is a priority for the international community. The World Organisation for Animal Health (WOAH) outlines a set of minimum competencies veterinarians need to support National Veterinary Services effectively. To improve the quality of veterinary education, Ethiopia has developed a new 2020 national curriculum that is harmonized with the WOAH competencies. A mixed methods needs assessment was conducted to identify barriers and challenges that Ethiopian veterinary medicine programs have faced in implementing the new WOAH-harmonized national curriculum. Representatives from active veterinary programs granting a Doctor of Veterinary Medicine (DVM) degree were invited to share their experiences via an online survey and follow-up focus group discussion. Fourteen veterinary programs, representing 93% of eligible programs nationwide, participated in the needs assessment. Quantitative analysis indicated that the most difficult topics associated with the new curriculum included Organization of Veterinary Services (Competency 3.1), Inspection and Certification Procedures (3.2), and practical applications of the regulatory framework for disease prevention and control (multiple competencies). Challenges associated with specific instructional methodologies, particularly the facilitation of off-site (private and public sector) student training, were also perceived as barriers to implementation. Focus group discussions elucidated reasons for these challenges and included limitations in faculty expertise, resource constraints (e.g., supplies, infrastructure), and access to off-site facilities for hands-on teaching. The results of this needs assessment will be used to identify and prioritize solutions to implementation challenges, helping Ethiopian veterinary medicine programs move the new WOAH-harmonized curriculum from theory to practice. As veterinarians are integral partners in advancing One Health, strengthening the capacity of Veterinary Services can ultimately safeguard animal and human health, grow economies, and improve lives.